2019
DOI: 10.1016/j.vaa.2018.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Alfaxalone for total intravenous anaesthesia in horses

Abstract: To determine the suitability of alfaxalone total intravenous anaesthesia in horses and concurrently evaluate infusion rates, cardiovascular effects, pharmacokinetics and the quality of the anaesthetic recovery period. Study Design Prospective, experimental study. Animals Eight Standardbred horses. Methods Horses were premedicated with intravenous (IV) acepromazine (0.03 mg kg-1) and xylazine (1 mg kg-1) and anaesthesia was induced with guaifenesin (35 mg kg-1) and alfaxalone (1 mg kg-1). Anaesthesia was mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…It was reported that the majority of horses anesthetized with alfaxalone 3.0 mg/kg/hr CRI for 3 hr showed excitement and hyperesthesia shortly after the cessation of alfaxalone infusion [ 12 ]. These undesirable behaviors were not observed in horses anesthetized with AGM-TIVA, and this was possibly due to the fact that the total infusion dose of alfaxalone was much lower in these horses than those used in a previous report [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the majority of horses anesthetized with alfaxalone 3.0 mg/kg/hr CRI for 3 hr showed excitement and hyperesthesia shortly after the cessation of alfaxalone infusion [ 12 ]. These undesirable behaviors were not observed in horses anesthetized with AGM-TIVA, and this was possibly due to the fact that the total infusion dose of alfaxalone was much lower in these horses than those used in a previous report [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the majority of horses anesthetized with alfaxalone 3.0 mg/kg/hr CRI for 3 hr showed excitement and hyperesthesia shortly after the cessation of alfaxalone infusion [ 12 ]. These undesirable behaviors were not observed in horses anesthetized with AGM-TIVA, and this was possibly due to the fact that the total infusion dose of alfaxalone was much lower in these horses than those used in a previous report [ 12 ]. On the other hand, Goodwin et al [ 13 ] reported that the horses anesthetized with infusions of alfaxalone (2.0 mg/kg/hr CRI) and medetomidine (5.0 µ g/kg/hr CRI) for 45 min stood on their first attempt and their recoveries were judged good to excellent.…”
Section: Discussionmentioning
confidence: 99%
“…(42) Propofol-ketamine anesthesia for internal fixation of fractures in racehorses [199] (43) Total intravenous anaesthesia in horses using medetomidine and propofol [200] (44) Anesthetic and cardiopulmonary effects of total intravenous anesthesia using a midazolam, ketamine and medetomidine drug combination in horses [201] (45) Alfaxalone in cyclodextrin for induction and maintenance of anaesthesia in ponies undergoing field castration [202] (46) Pharmacokinetic profile in relation to anaesthesia characteristics after a 5% micellar microemulsion of propofol in the horse [203] (47) Evaluation of cardiovascular, respiratory and biochemical effects, and anesthetic induction and recovery behavior in horses anesthetized with a 5% micellar microemulsion propofol formulation [204] (48) Clinical evaluation of total intravenous anesthesia using a combination of propofol and medetomidine following anesthesia induction with medetomidine, guaifenesin and propofol for castration in Thoroughbred horses [205] (49) Evaluation of a midazolam-ketamine-xylazine infusion for total intravenous anesthesia in horses [206] (50) Alfaxalone and medetomidine intravenous infusion to maintain anaesthesia in colts undergoing field castration [207] (51) Clinical and pharmacokinetic evaluation of S-ketamine for intravenous general anaesthesia in horses undergoing field castration [208] (52) Cardiovascular effects of total intravenous anesthesia using ketamine-medetomidine-propofol (KMP-TIVA) in horses undergoing surgery [209] (53) Cardiorespiratory and anesthetic effects of combined alfaxalone, butorphanol, and medetomidine in Thoroughbred horses [210] (54) Total intravenous anesthesia using a midazolam-ketamine-xylazine infusion in horses: 46 cases (2011-2014) [211] (55) Alfaxalone for total intravenous anaesthesia in horses [212] 5 /…”
Section: Loe and Topic Referencesmentioning
confidence: 99%
“…Schwarz et al, (2014) established a minimum infusion rate (MIR) of 10 mg/kg/h (0.18 mg/kg/min) for TIVA with alfaxalone as a sole agent in cats (Schwarz et al, 2014). Conversely, a lower infusion rate (3 mg/ kg/h or 0.05 mg/kg/min) has been shown to maintain an adequate depth of anesthesia in horses (Goodwin et al, 2018). Nevertheless, Ndawana et al, (2014) showed that a MIR of 0.16 mg/kg/min (10 mg/kg/h) of alfaxalone was feasible to prevent gross movement of trunk, head or limbs after supramaximal noxious stimuli in goats.…”
Section: Figure 2 Graphical Representation (From Top Left To Bottom mentioning
confidence: 99%
“…Furthermore, alfaxalone administered in either boluses or CRI for TIVA may cause hypotension in cats (Beths et al, 2014;Schwarz et al, 2014). However, either no side effects or minimal changes in the hemodynamic parameters have been shown after alfaxalone CRI in dogs (Ambros et al, 2008) and horses (Goodwin et al, 2018). While balanced cardiovascular parameters have been recorded during TIVA with alfaxalone CRI in goats (Ndawana et al, 2014), a delayed hypotensive state (between 45 and 75 minutes after the start of the alfaxalone CRI) has been demonstrated in desflurane-anesthetized sheep (Granados et al, 2012).…”
Section: Figure 2 Graphical Representation (From Top Left To Bottom mentioning
confidence: 99%